Heutagogy in Arabic Class: How It Is Applied in The Islamic Education Study Program Of Universitas Islam Riau - Saproni Muhammad Samin (ALSINATUNA, 2019)
This study aims to uncover the purpose of teaching Arabic in the Islamic Education Study Program at Universitas Islam Riau and the possibility of implementing a heutagogical approach in the said course. Heutagogy is the latest approach in the world of Education, which is in line with the era of the Industrial Revolution 4.0. It is a qualitative research using descriptive analysis method. Data collection in this research was carried out in three ways, i.e. interview, documentation, and library research. From the analysis, the study concludes that the general objective of the teaching of Arabic in the Islamic Education Study Program at Universitas Islam Riau is that students are able to recognize Arabic grammar and practice it in the writing and reading of religious texts and other Arabic texts; besides, students are expected to be able to understand the Arabic book, speak, and write Arabic in simple situations. The next conclusion shows that the heutagogical approach cannot be fully applied in Arabic class in the Islamic Education Study Program because the purpose of the Arabic learning cannot come out of the goals set by the study program. However, the spirit of heutagogy can be seen in the Arabic learning process